2020
DOI: 10.4236/ojbm.2020.82024
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Consumer Impulsive Purchasing Behaviour in Medium-Large Shopping Malls in Ghana

Abstract: This research examines the determinants of consumer impulsive purchasing behaviour of Ghanaian shoppers. Churchill's and Peter's [1] conceptual model was adapted and modified as the study proposed model to verify empirical data. A sample size of 129 out of 180 was obtained from Ghanaian shoppers at medium shopping malls located in Accra and Kumasi cities in February, 2019 using a survey method. Data analysis was performed using AMOS in Statistical Packages for Social Sciences' (SPSS) software. Correlational an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Previous studies consistently demonstrated the significant influence of store atmosphere on consumers' impulsive buying, indicated by impulsive purchases in the store (Arthur et al, 2020;Sindhu & Kloep, 2020). Furthermore, store atmosphere significantly affects positive emotion, and positive emotion mediates the impact of store atmosphere on impulsive buying (Aurellia, 2019).…”
Section: Store Atmospherementioning
confidence: 83%
“…Previous studies consistently demonstrated the significant influence of store atmosphere on consumers' impulsive buying, indicated by impulsive purchases in the store (Arthur et al, 2020;Sindhu & Kloep, 2020). Furthermore, store atmosphere significantly affects positive emotion, and positive emotion mediates the impact of store atmosphere on impulsive buying (Aurellia, 2019).…”
Section: Store Atmospherementioning
confidence: 83%
“…The Ghanaian apparel marketplace is unique but similar to what pertains to other consumer societies. It has evolved from open-air markets through in-store such as department stores, speciality stores, supermarkets and shopping malls (Arthur et al , 2020) to online markets (Mintah, 2018). The Ghanaian fashion industry is dominated by businesses that produce custom-made garments (Sarpong et al , 2011).…”
Section: Literature Reviewmentioning
confidence: 99%